PENENTUAN KEPUTUSAN INVESTASI SAHAM SUB SEKTOR PERKEBUNAN BERDASARKAN CAPITAL ASSET PRICING MODEL (CAPM) - Posma Sariguna Johnson Kennedy; Anatasya Yanis (Institut Informatika Dan Bisnis (IIB) Darmajaya, 2019)
The purpose of this study is to analyze a stock investment decision by applying the capital asset pricing model. This study uses a quantitative descriptive method with a sample of 15 companies in the plantation sub-sector on the Indonesia Stock Exchange in the period January 2014 to December 2016. In this study, no hypothesis testing was conducted, but rather describing an object systematically. The results of data processing show which stocks are worth undervalued or overvalued, as well as an overview of the balance of the security market line of these shares. The results of the study showed that there were seven company stocks classified as undervalued by investment decisions to buy shares. While eight other companies are classified as too high or overvalued, the investment decision is to sell shares.Keywords - systematic risk, capital asset pricing model, security market line, undervalued, overvalued